Spatial ecology and population trends of the scavengers (Aves: Falconiformes) in Azerbaijan - Arzu F. Mammadov; Tahir A. Karimov; Alex V. Matsyura; Dashgin Sh. Ganbarov (Acta Biologica Sibirica, 2025)
Avian scavengers in Azerbaijan, including the Griffon Vulture (Gyps fulvus), Black Vulture (Aegypius monachus), Egyptian Vulture (Neophron percnopterus), and Bearded Vulture (Gypaetus barbatus), are experiencing significant population declines, with a 15.3% reduction in breeding pairs documented between 2012 and 2024. This study presents the first comprehensive assessment of their nesting ecology, population trends, and anthropogenic threats across Azerbaijan’s three major mountain regions: the Greater Caucasus, Lesser Caucasus, and Talysh Mountains. Systematic surveys of 33 nesting sites revealed distinct spatial and elevational segregation, with 60.6% of nests located in the Lesser Caucasus, 36.3% in the Greater Caucasus, and 3.0% in the Talysh Mountains. Species exhibited pronounced stratification by elevation: Bearded Vultures nested exclusively above 2000 m, Griffon and Egyptian Vultures occupied mid-elevation zones (500–1800 m), and Black Vultures were restricted to lowland forests (<500 m). The primary drivers of decline were linked to anthropogenic factors, including a 28.5% reduction in livestock populations, which diminished carrion availability, and a 15.7% expansion of agricultural lands, which reduced foraging habitats. Direct threats such as nest destruction, poaching, and incidental capture for commercial use further exacerbated declines, particularly for Black Vultures in the Talysh Mountains, where only a single breeding cluster remains. Breakpoint analysis identified critical years of accelerated decline: 2018 for Griffon Vultures and 2015 for Black Vultures, coinciding with regional reductions in wild ungulate populations and increased human disturbance. Comparative analysis with global datasets revealed parallels to declines observed in Mediterranean and South Asian vulture populations, though Azerbaijan’s unique socioecological context, including post-Soviet land-use changes and its role as a migratory corridor, demands tailored conservation strategies. We propose urgent interventions, including supplemental feeding programs, habitat protection in the Lesser Caucasus, and mitigation of power line collisions, informed by successful case studies from Europe. These findings underscore Azerbaijan’s importance as a critical stronghold for vulture conservation in the Caucasus and highlight the need for transboundary cooperation to safeguard these keystone scavengers.